2001
DOI: 10.1002/jmv.1045
|View full text |Cite
|
Sign up to set email alerts
|

Symptom pathogenesis during acute influenza: Interleukin‐6 and Other cytokine responses

Abstract: In experimental human influenza infection initiated by nasal inoculation, the magnitude of viral replication, fever, and symptoms correlate with nasopharyngeal lavage fluid levels of various cytokines. Our aim was to assess these relationships in patients with naturally occurring acute influenza. Patients with culture-positive influenza illness of less than 36 hr of duration were studied. Nasopharyngeal washing were collected at enrollment and on Day 2, 4, 6 and 8 for quantitative virus isolation and IL-6, TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
228
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(249 citation statements)
references
References 20 publications
18
228
1
2
Order By: Relevance
“…However, it should be noted that NK cells are abundant in inflamed and noninflamed human lymph nodes (71,72) and thus may exert a rapid antiviral effect. Fast-replicating viruses such as IAV reach significant viral titers within 24 h of infection (73); human NK cells respond within 24 h to IAV (47); and IFN-γ levels in nasopharyngeal lavage fluid correlate significantly to IAV titers, clinical symptoms, oral temperature, and nasal discharge (74). In addition to its anti-…”
Section: Hla-c1 Homozygous and Hla-c2 Homozygous Groups Appearedmentioning
confidence: 99%
“…However, it should be noted that NK cells are abundant in inflamed and noninflamed human lymph nodes (71,72) and thus may exert a rapid antiviral effect. Fast-replicating viruses such as IAV reach significant viral titers within 24 h of infection (73); human NK cells respond within 24 h to IAV (47); and IFN-γ levels in nasopharyngeal lavage fluid correlate significantly to IAV titers, clinical symptoms, oral temperature, and nasal discharge (74). In addition to its anti-…”
Section: Hla-c1 Homozygous and Hla-c2 Homozygous Groups Appearedmentioning
confidence: 99%
“…In the influenza infection cytokines are produced locally and systemically and their production is important in promoting host-immune defense to alleviate symptoms especially in the early stage of infection (Hayden et al, 1998;Kaiser et al, 2001;Cheung et al, 2002;Van Reeth, 2002). In a murine model, cytokines such as IL-12 and IL-18 as Th1 immune-response mediators, IFN-γ as a Th1 cytokine, IL-4 and IL-10 as Th2 cytokines, IL-1α, IL-1β, IL-6, and TNF-α as inflammatory cytokines, and IFN-α, -β have been shown to be produced in the respiratory tract during infection (Hennet et al, 1992;Kurokawa et al, 1996aKurokawa et al, ,b, 2002Tsurita et al, 2001;Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…IL-12 is a strong inducer of IFN-γ and is important in the development of Th1 cells followed by the generation of cell-mediated immunity contributing to the elimination of influenza virus (Monteiro et al, 1998). IL-18, a novel cytokine with potent IFN-γ-inducing activity, plays an important role in NK cell activity and the Th1-mediated immune response in collaboration with IL-12 (Kaiser et al, 2001;Tsurita et al, 2001;NeffLaFord et al, 2003;Liu et al, 2004). Kaiser et al (2001) reported that the magnitude of the early decrease in viral titers correlated with initial levels of IFN-γ in nasopharyngeal lavage fluid of human volunteers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such rapid induction of humoral responses is not only consistent with a local protective role for Abs during a primary infection, it also indicates that local B cell responses are initiated during the acute innate cytokine response. Cytokines induced rapidly to the virus in the respiratory tract include type I IFN, IL-1, IL-6, and TNF-␣ (13,14). The potential role and the effects such innate immune stimuli might have on B cell responsiveness to subsequent encounter with Ag and/or Th cells has received little attention in the past.…”
mentioning
confidence: 99%